Art of TIL immunotherapy: SITC’s perspective on demystifying a complex treatment - Robert Brown; Marco Donia; Simon Turcotte; George Coukos; John Mullinax; Brian Gastman; James C Yang; Michael T Lotze; John B A G Haanen; Inge Marie Svane; Stephanie L Goff; Vernon K Sondak; et al. (Journal for ImmunoTherapy of Cancer)
In a first for solid cancers, cellular immunotherapy has entered standard of care in the treatment of patients with metastatic melanoma. The infusion of autologous tumor-infiltrating T lymphocytes (TIL) is capable of mediating durable tumor regression and is now Food and Drug Administration-approved for patients with disease refractory to immune checkpoint inhibitors. Since the advent of chimeric antigen receptor (CAR) T cells for patients with hematological malignancies, a growing network of centers capable of delivering effector T cell products to patients has developed. Administration of TIL can be layered onto that institutional framework, but there are many complex and unique aspects to TIL immunotherapy. The highly multidisciplinary clinical expertise and coordination required to successfully and safely deliver TIL to patients began within the National Cancer Institute Surgery Branch and have been subsequently adopted worldwide. The general steps, most of which require hospital inpatient resources, include a surgical procedure to harvest sufficient tumor for TIL manufacturing, admission for non-myeloablative lymphodepleting chemotherapy followed by TIL, and intravenous interleukin-2 (IL-2, aldesleukin). Here, we provide the principles, practice, and required resources underlying the efficient and safe delivery of TIL immunotherapy derived from the clinical expertise of high-volume centers around the world. This article enhances published clinical practice guidelines by providing underlying clinical rationale and data-driven examples to demystify TIL immunotherapy in order to facilitate uptake and improve patient access to this promising treatment modality in clinical and research settings.